2014
DOI: 10.1016/j.jtcvs.2013.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microRNA-145 to prevent vein graft disease in rabbits by regulation of smooth muscle cell phenotype

Abstract: Nonviral transduction of miR-145 into the bypass graft could be a novel option for preventing intimal hyperplasia in vein graft disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Ohnaka et al . [18] revealed that upregulation of miR-145 induced the phenotypic transformation of vascular smooth muscle cells in rabbit vein graft models. The study focused on the effects of miRNAs in endothelial dysfunction induced by mechanical stretch.…”
Section: Discussionmentioning
confidence: 99%
“…Ohnaka et al . [18] revealed that upregulation of miR-145 induced the phenotypic transformation of vascular smooth muscle cells in rabbit vein graft models. The study focused on the effects of miRNAs in endothelial dysfunction induced by mechanical stretch.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, increased VSMC proliferation is cause of vein graft stenosis and failure. In line, the transduction of miR-145 into a rabbit vein used for bypass grafting prevented vein graft disease by regulation of VSMC phenotype [47]. On the other side, miR-143/ 145 deficiency was reported to attenuate the progression of plaque formation in a mouse model of atherosclerosis [48], indicating that more research is necessary to clarify the role on this miRNA cluster in vascular disease.…”
Section: Mirna Expressed In Vascular Cellsmentioning
confidence: 99%
“…Circulating levels of some miRs were down-regulated in patients with coronary artery disease [6], and the patients with type 2 diabetes had less circulating endothelial miR-126 [7]. In vitro experiments showed that miR-125b [1, 8], miR-145 [9] and miR-146a [10] played a regulative role in the aberrant VSMC proliferation, which is a key pathological process of proliferative vascular diseases, such as atherosclerosis or vascular calcification.…”
Section: Introductionmentioning
confidence: 99%